Envisioning america’s third civilization: Colombia at the international exhibitions of madrid and chicago (1892-1893) (2020)
Objective/Context: In the context of the Fourth Centenary of the discovery of America, Colombia participated in the Historical American Exposition in Madrid (1892) as well as the Chicago World’s Columbian Exposition (1893). On both occasions, the focus was on pre-Hispanic objects. Through the glorification of the pre-Columbian past, the Colombian exhibition organizers sought to endow their country with an “antiquity” of its own, comparable to the ancient civilizations of Peru and Mexico. Apart from this, they projected the image of a modern nation through the scientific treatment of such vestiges of the past. Originality: Traditionally, the study of international exhibitions has focused on the projection of national self-images. However, besides their relevance for the process of nation-building, we also understand them as transnational platforms that fostered the circulation of knowledge and objects. Methodology: Using the historical-critical method, we rely on primary sources from Colombia, Spain and the United States, including archival material, but also newspaper articles, catalogs and conference proceedings. The archival material is especially helpful for understanding the organizational processes behind the exhibitions, which is the reason behind our focus on the correspondence exchanged between the delegates and the Colombian government. On the other hand, newspaper articles, catalogs and conference proceedings give us an idea of the various forms of presentation employed, as well as the reception by the public. Conclusions: The fact that Colombia has been concerned with organizing international presentations that consisted predominantly of pre-Columbian objects, shows the importance the study of the past had gained by the end of the 19th century. Although the pre-Columbian past was not integrated into the national imaginary at the time, its scientific study, and its presentation abroad, laid the foundations for its future nationalization. © 2020, Universidad de los Andes, Bogota Colombia. All rights reserved.